The Forgotten Pirates: Iraqi and Iranian Pirates in the Arabian Gulf Who Have Never Been Reported to the International Maritime Bureau. (4th May 2018) - Alqattan, Mohammad E. A.; Gray, Tim; Stead, Selina M.
ABSTRACT: If piracy attacks are unreported, a misleading impression is given of piracy situations in regions where there could be serious consequences for ships traveling in waterways on the assumption that they are piracy-free waters. However, sometimes not reporting piracy attacks could help to contain piracy before it expands, because reporting can lead to the media over-focusing on piratical incidents, and armed guards being deployed on ships, which causes pirates to use heavier arms and escalates the level of conflict. Piracy that took place during 2003–2012 in the north and the center of the Arabian Gulf has never been reported to the International Maritime Bureau. The present article examines this case of unreporting, and discusses its causes and consequences.